The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4236/ajibm.2017.76053
|View full text |Cite
|
Sign up to set email alerts
|

Examining Factors Influencing E-Banking Adoption: Evidence from Bank Customers in Zambia

Abstract: This paper contributes to the electronic banking (e-banking) literature by applying the modified Technology Acceptance Model (TAM) in an under-researched Zambian context. Specifically, it examines the influence of e-banking technology's perceived usefulness, perceived ease of use and trust (safety and credibility) on e-banking adoption. Based on a quantitative correlational design, primary sample data were collected from 222 bank customers from two of Zambia's largest cities. The findings indicate that the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…In the hypothesis (H5) it can be concluded that intention tends to mediate the relationship between behavioral variables on the implementation of usage behavior, thus making intention a variable that can predict future actions. The results of this study are in line with previous studies (Yu, 2012); (Farah et al, 2018); (Mwiya et al, 2017); (Kwateng et al, 2019); (Prabawalingga & Yadnyana, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In the hypothesis (H5) it can be concluded that intention tends to mediate the relationship between behavioral variables on the implementation of usage behavior, thus making intention a variable that can predict future actions. The results of this study are in line with previous studies (Yu, 2012); (Farah et al, 2018); (Mwiya et al, 2017); (Kwateng et al, 2019); (Prabawalingga & Yadnyana, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Perceived transaction security The development of digital technologies in the banking field implies the implementation of mechanisms focused on security (Mwiya et al, 2017). As the level of control of the technology does not belong to the user, the person relies on the measures provided to him, such as authentication, passwords, and confidentiality clauses (Zimmermann & Gerber, 2020).…”
Section: Technological Features Trust and Use Of E-banking Servicesmentioning
confidence: 99%
“…This study is empirical study conducted for investigating bankers' prospective or views on e-banking and they found that bankers' are convinced that e-banking helps to improve the relationship between banker and costumer. Bruce Mwiya et al (2017) examined the influence of e-banking technology's perceived usefulness, perceived ease of use and trust (safety and credibility) on e-banking adoption. Mahesh Kumar and Sanjay Gupta (2020) investigated ebanking users' perception with regard to online risk for public, private and foreign banks in India.…”
Section: Review Of Literature: A) Perceptions About E-bankingmentioning
confidence: 99%